2022
DOI: 10.18488/5008.v10i1.4416
|View full text |Cite
|
Sign up to set email alerts
|

Is Life Insurance Crucial to Society and the Economy? Evidence from Asian Countries both before and after the Global Financial Crisis

Abstract: Life insurance is not merely vital for the economic development of a country but also the health of an individual’s financial circumstances. This study examines the income elasticity of life insurance consumption and the impact of life insurance markets on economic growth in 22 Asian countries from 2001 to 2016. According to a panel data analysis of life insurance demand, it is inelastic in proportion to GDP per capita, implying that the product is a necessity for Asians. Furthermore, the results of a life ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Lee et al (2018) found that as income increases, individuals tend to consume more and invest in their human capital, which results in a greater demand for insurance to safeguard their future earnings and the anticipated consumption of their beneficiaries. Therefore, the GDPPC has a positive effect on life insurance (Hassan 2022).…”
Section: Resultsmentioning
confidence: 97%
“…Lee et al (2018) found that as income increases, individuals tend to consume more and invest in their human capital, which results in a greater demand for insurance to safeguard their future earnings and the anticipated consumption of their beneficiaries. Therefore, the GDPPC has a positive effect on life insurance (Hassan 2022).…”
Section: Resultsmentioning
confidence: 97%